Intensity‐dependent modulatory effects of vagus nerve stimulation on cortical excitability. (25th April 2013) - Mollet, L.; Grimonprez, A.; Raedt, R.; Delbeke, J.; El Tahry, R.; De Herdt, V.; Meurs, A.; Wadman, W.; Boon, P.; Vonck, K.
Abstract : Objectives: Vagus nerve stimulation (VNS) is an effective treatment for refractory epilepsy. It remains unknown whether VNS efficacy is dependent on output current intensity. The present study investigated the effect of various VNS output current intensities on cortical excitability in the motor cortex stimulation rat model. The hypothesis was that output current intensities in the lower range are sufficient to significantly affect cortical excitability. Material and methods: VNS at four output current intensities (0 mA, 0.25 mA, 0.5 mA and 1 mA) was randomly administered in rats ( n = 15) on four consecutive days. Per output current intensity, the animals underwent five‐one‐hour periods: (i) baseline, (ii) VNS1, (iii) wash‐out1, (iv) VNS2 and (v) wash‐out2. After each one‐hour period, the motor seizure threshold (MST) was measured and compared to baseline (i.e. ∆MSTbaseline, ∆MSTVNS 1, ∆MSTwash‐out1, ∆MSTVNS 2 and ∆MSTwash‐out2 ). Finally, the mean ∆MSTbaseline, mean ∆MSTwash‐out1, mean ∆MSTwash‐out2 and mean ∆MSTVNS per VNS output current intensity were calculated. Results: No differences were found between the mean ∆MSTbaseline, mean ∆MSTwash‐out1 and mean ∆MSTwash‐out2 within each VNS output current intensity. The mean ∆MSTVNS at 0 mA, 0.25 mA, 0.5 mA and 1 mA was 15.3 ± 14.6 μA, 101.8 ± 23.5 μA, 108.1 ± 24.4 μA and 85.7 ± 18.1 μA respectively. The mean ∆MSTVNS at 0.25 mA, 0.5 mA and 1 mA were significantly larger compared to the mean ∆MSTVNS at 0 mA ( P = 0.002 for 0.25 mA; P = 0.001 for 0.5 mA; P = 0.011 for 1 mA). Conclusions: This study confirms efficacy of VNS in the motor cortex stimulation rat model and indicates that, of the output current intensities tested, 0.25 mA is sufficient to decrease cortical excitability and higher output current intensities may not be required.